SHIFTWORK AS ONE OF RISK FACTORS OF ARTERIAL HYPERTENSION AND METABOLIC DISORDERS - I. S. Dzherieva; N. I. Volkova; S. I. Rapoport (Столичная издательская компания, 2015)
Background. Shiftwork is considered as one of risk factors of arterial hypertension (HT) and metabolic disorders. Aim. To study effects of different types of shift plan on HT and the metabolic disorders development. Material and Methods. 1091 men were included in the study. Patients were split into subgroups according to age (20-29, 30-39, 40-49, 50-59 years old) and shift plan (steady or shiftable work schedule). HT (blood pressure >130/85 mm Hg), abdominal obesity (waist circumference >94 cm), disorders of glucose metabolism were revealed. Results. HT prevalence in patients with shiftwork was significantly higher than that in employees with steady work schedule (34.4 vs 27.4%, respectively; р<0.01). In patients with shift and steady work schedule significant differences in abdominal obesity (69.2 vs. 19.3%, respectively; p<0.001) and glucose metabolism disorders rates (19.0 vs. 10.6%, respectively; p<0.001) were also found. Differences between groups in prevalence of hypercholesterolemia and metabolic disorders cluster were not significant. HT associated with metabolic disorders dominated among steady work patients aged 40-49 years (56.7%) in comparison with shiftable work patients (20.0%), p<0.01. Conclusion. Shiftwork may be considered as a risk factor of HT and metabolic disorders in males.